Schoolishness : alienated education and the quest for authentic, joyful learning / Susan D. Blum. - Blum, Susan Debra (Cornell University Press, 2024)
"In Schoolishness , Susan D. Blum continues her journey as an anthropologist and educator. The author defines "schoolishness" as educational practices that emphasize packaged "learning," unimaginative teaching, uniformity, constant evaluation by others, arbitrary forms, predetermined time, and artificial boundaries, resulting in personal and educational alienation, dependence, and dread. Drawing on critical, progressive, and feminist pedagogy in conversation with the anthropology of learning, and building on the insights of her two previous books Blum proposes less-schoolish ways of learning in ten dimensions, to lessen the mismatch between learning in school and learning in the wild. She asks, if learning is our human "superpower," why is it so difficult to accomplish in school? In every chapter Blum compares the fake learning of schoolishness with successful examples of authentic learning, including in her own courses, which she scrutinizes critically. Schoolishness is not a pedagogical how-to book, but a theory-based phenomenology of institutional education. It has moral, psychological, and educational arguments against schoolishness that, as Blum notes, "rhymes with foolishness."--publisher.
Keywords: Learning.; Education -- Social aspects.; Educational anthropology.